Relação entre mobilidade acadêmica internacional e inovação : impactos nos países de origem e destino dos pesquisadores - Siekierski, Paulette (2018)
The main objective of this PhD thesis was to understand the relation between international mobility of academics (IMA) and innovation, and its impacts on the countries of origin and destination of researchers. For this purpose three diverse and complementary articles were developed with specific methodologies through which deepens relevant aspects of the proposed discussion. The aim of the first article was to perform a meta-analysis in order to understand the relation between IMA with variables, proxies of innovation, and their impacts in the countries of destination, origin, and destination and origin simultaneously of the researchers. After the elaboration of a rigorous research protocol from 36 articles selected in 15 top journals of the Scopus and ISI Web of Science databases, 20 variables were identified, including five of them, with positive, negative or null impacts for the countries. The study brings contributions to the academy insofar as IMA generates innovation through the development of research networks, the increase of publications with better quality, the increase of citations, and the generation of partnerships between universities, industries and laboratories that can improve education and science. Knowing the types of innovation that IMA generates enables governments that wish to invest in scientific, technological, economic and social development to choose the best measures of attraction and retention of brains. For industry, technological catch-up and highly skilled labour (HSL), means enhancing competitiveness and capacity building, growth of research and development (R&D), creating new products, patent filing, increased investments and expansion of internationalization. The objective of the second research was to investigate which of the following factors is most important in the academics mobility decision: the impact of the science, technology and innovation (ST&I) infrastructure, or the quality of life in the host country. Were considered journals of scientific prestige and research and development (R&D) institutions as proxies for ST&I and the human development index (HDI) as a proxy for quality of life. These data came from several databases. The results of a multiple linear regression show that, although the ST&I infrastructure takes precedence over quality of life, both are influential factors in academics mobility decisions. The results offer guidance for academics in their decisions regarding mobility, as well as offering guidance for government policy-makers with regard to national investments to address brain drain and brain gain. The third study aimed to investigate the relation between patent filing, proxy for innovation, with IMA, education and applied research. For this purpose, primary databases at the National Institute of Industrial Property (INPI), and secondary databases of the Lattes Platform, Linkedin and Foundation for Research Support of the State of São Paulo (FAPESP) were carried out. The first two Brazilian universities according to the INPI (2014) patent ranking were the University of São Paulo (USP), with a universe of 282 inventors who filed 78 patents followed by the University of Campinas (UNICAMP) with a universe of 190 inventors who filed 60 patents. The results show a positive relation between the number of patents deposited with education, participation in IMA programs and applied research.